Community Education: Raising Awareness and Knowledge About Japanese Encephalitis Vaccination in Community Health Center Areas - Nuruniyah, Nuruniyah; Meilantika, Ayu Diana; Khairillah, Yuyun Nisaul; Ramanda, Galih Dwiki; Hastuti, Lidia (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2024)
The JE virus can be transmitted from animals to humans through a vector in the form of the Culex tritaeniorhynchus mosquito. JE virus infection attacks parts of the brain and can occur because the body does not have JE-specific antibodies. Vaccination has been shown to be an effective method in preventing JE disease and is given to children aged 9 months to 15 years Metode dalam pengabdian ini yaitu dengan memberikan edukasi mengenai vaksinasi JE, dengan melakukan persiapan dan pelaksanaan yang telah disetujui oleh mitra. Adapun hasil dari setelah masyarakat diberikan edukasi tentang vaksinasi JE terjadi peningkatan pengetahuan yang dapat dilihat dari hasil kuisioner pre test pengetahuan sebesar 45% dan meningkat setelah diberikan pengetahuan sebesar 84,45%. The successful Community Service Program can be seen from the results of the level of community knowledge. The suggestion in the next service is that it can be continued with JE immunization monitoring which can be seen from the maternal and child health book, so that it can be seen whether the coverage of JE vaccination has increased from the vaccine target of the Tambelan Sampit health center.